Teaching Children Science: An Inquiry Approach - Kuslan, Louis I. (Wadsworth Pub. Co, 1972)
Keywords: Science; Study and teaching (Elementary); Learning by discovery; dept.nhstc; faculty_collection

Connecticut Science, Technology, and Medicine in the Era of the American Revolution - Kuslan, Louis I. (American Revolution Bicentennial Commission of Connecticut, 1978)
Keywords: Connecticut; History; History; Medicine; History; Technology; History; United States; Revolution; 1775-1783; Science; dept.nhstc; faculty_collection

Robert Boyle, the Great Experimenter, - Kuslan, Louis I.; Stone, A. Harris (Prentice-Hall, 1970)
The life of the seventeenth-century scientist best known for his analysis of pressure and volume in gases and for his example to fellow scientists in sharing his discoveries with them.
Keywords: Boyle; Robert; 1627-1691; Chemists; Children's literature; dept.che; dept.nhstc; faculty_collection